circKLF4 Upregulates Klf4 and Endoglin to Promote Odontoblastic Differentiation of Mouse Dental Papilla Cells via Sponging miRNA-1895 and miRNA-5046 - Zhang, Yue; Zhang, Hao; Yuan, Guohua; Yang, Guobin (Frontiers in Physiology, 2022)
circular RNAs (circRNAs) is a broad and diverse endogenous subfamily of non-coding RNAs, regulating the gene expression by acting as a microRNA (miRNA) sponge. However, the biological functions of circRNAs in odontoblast differentiation remain largely unknown. Our preliminary study identified an unknown mouse circRNA by circRNA sequencing generated from mouse dental papilla and we termed it circKLF4. In this study, quantitative real-time PCR and in situ hybridization were used and demonstrated that circKLF4 was upregulated during odontoblastic differentiation. Gene knockdown and overexpression assays indicated that circKLF4 promoted odontoblastic differentiation of mouse dental papilla cells (mDPCs). Mechanistically, we found that circKLF4 increased the linear KLF4 expression in a microRNA-dependent manner. By mutating the binding sites of microRNA and circKLF4, we further confirmed that circKLF4 acted as sponge of miRNA-1895 and miRNA-5046 to promote the expression of KLF4. We then also found that ENDOGLIN was also up-regulated by circKLF4 by transfection of circKLF4 overexpression plasmids with or without microRNA inhibitor. In conclusion, circKLF4 increases the expression of KLF4 and ENDOGLIN to promote odontoblastic differentiation via sponging miRNA-1895 and miRNA-5046.